Avaliação zootécnica e econômica da restrição alimentar programada na produção de tilápias (Oreochromis niloticus) em tanques-rede - Frederico Ozanam de Souza (2017)
As in the production of terrestrial animals, in fish farming, food is among the main expenses for the producer. Therefore rationalization of the use of rations is fundamental for the good economic performance of the productive systems. The objective of this work was to evaluate the adoption of feeding plans with food restriction for tilapia. The experiment was carried out in the Furnas-Brasil reservoir in 20 net cages of 3.0 m³ with 300 fish each. The initial weight of the fish was 201 ± 10 g and the experimental period was 98 days. The experiment was carried out in a completely randomized design, with five treatments and four replications. The treatments were different food plans: 1- Continuous feeding (control); 2- Six consecutive feeding days, followed by one day of feed restriction and controlled feedback; 3- Six consecutive feeding days, followed by one day of feed restriction and feedback at will; 4- Five consecutive feeding days, followed by two days of feed restriction and controlled feedback; 5- Five consecutive feeding days, followed by two days of feed restriction and feedback at will. Weight gain, feed conversion, serum biochemical profile and financial viability during a fattening cycle of tilapia were measured. At the end of the experimental period all fish were weighed for performance evaluation and three fish per experimental unit were anesthetized for blood collection and euthanized for body composition evaluation. Treatments 3 and 5 presented better results in weight gain and biomass, but were those that presented worse feed conversion and production cost. Treatments 2 and 4 did not differentiate in weight gain and biomass of the control group, but presented lower consumption, feed conversion and higher financial return. There was no significant difference in the biochemical serum profile nor in the body composition. It is concluded that in field situations where there is no strict control as in experiment, it is recommended that one day of food restriction be used, followed by controlled feedback according to the manufacturers table